Fine needle aspiration cytology in the diagnosis of canine cutaneous transmissible venereal tumor: case report - Rocha, Noeme Sousa [UNESP]; Tremori, Tália Missen [UNESP]; Carneiro, João Alexandre Matos [UNESP] (Scientific Research Publishing, 2014)
Fine needle aspiration cytology (FNAC) has been widely used in the diagnosis of lesions from various origins, especially neoplastic. The technique is simple, fast, safe, minimally invasive and inexpensive, which allows through the evaluation of cell morphology to establish prognosis, delineate surgical margins, monitor lesion growth, validate indication euthanasia during surgery and monitor chemotherapy protocols. Diagnosis of canine transmissible venereal tumor (TVT) can be accomplished with ease and precision, even to be rated, according to the degree of aggressiveness. The study objective was to demonstrate the effectiveness of the examination in the diagnosis of TVT plasmacytoid type. An eight-month dog presented to the veterinary hospital (HV), faculty of veterinary medicine and animal science, FMVZ, UNESP-Univ Estadual Paulista with clinical suspicion of cutaneous lymphoma. By presenting multiple nodular lesions, FNAC was performed to cytological diagnosis. The tissue showed cells consistent with TVT. The animal was treated, and a total cure was achieved. According to the literature, TVT mainly affects external genitalia of sexually active animals and its transmission is more frequent during intercourse. In addition, animals sexually immature and without contact to the street dogs, hardly have injuries by TVT. In this case, verrucous and ulcerated lesions on the vulva of its mother during pregnancy and childbirth infected the animal. Diffuse and predominant dorsal injuries occurred due to both exfoliation of breast tumor during delivery and immunosuppression of pup at birth, thus favoring an atypical transmission.
Keywords: Cytological diagnosis; TVT; Atypical transmission